Neurolymphomatosis in primary cutaneous CD4+ pleomorphic small/medium-sized T-cell lymphoma mimicking Hansen's disease - Anza Khader; Mary Vineetha; Mamatha George; Shiny Padinjarayil Manakkad; Sunitha Balakrishnan; Uma Rajan (Wolters Kluwer Medknow Publications, 2017)
Neurolymphomatosis (NL) refers to nerve infiltration by neurotropic neoplastic cells in the setting of a known or an unknown hematological malignancy. It typically presents as painful or painless peripheral mononeuropathy, mononeuritis multiplex, polyneuropathy, polyradiculopathy, or cranial neuropathy. A 32-year-old male presented with a hyperpigmented hypoesthetic plaque over the anterolateral aspect of the right leg with thickening of the right common peroneal nerve and foot drop clinically diagnosed as Hansen's disease. Biopsy taken from skin showed infiltrates of pleomorphic small and medium sized lymphocytes in the dermis and subcutis. On immunohistochemistry, the cells were positive for CD3, CD4 and negative for CD8, CD20, and CD30. Ultrasonography-guided fine-needle aspiration of the thickened nerve showed infiltrates of atypical lymphoid cells. Based on these findings, a diagnosis of NL in primary cutaneous CD4+ pleomorphic small/medium-sized T-cell lymphoma was made. The disease responded to systemic chemotherapy and localized radiotherapy with no evidence of relapse during 3 years follow-up. NL in primary cutaneous CD4+ pleomorphic small/medium-sized T-cell lymphoma presenting with manifestations redolent of Hansen's disease is not described in available literature. This case also demonstrates the utility of fine needle aspiration of nerve, a minimally invasive procedure in the diagnosis of NL.